Age Group Differences in the Predictive Validity of the Level of Service Inventory–Revised. (December 2016) - Ellison, Jared M.; Steiner, Benjamin; Brennan, Pauline; Chenane, Joselyne L.
The Level of Service Inventory–Revised (LSI-R) is a widely used risk assessment tool with demonstrated predictive validity among incarcerated offenders. However, researchers have yet to examine the predictive validity of the LSI-R with adult inmates of different ages. We examined the predictive validity of the LSI-R and its 10 subcomponents across developmentally defined age groups of men confined in prisons in a Midwestern state. We found that the LSI-R predicted the prevalence of misconduct similarly across the groups, but there were a number of differences in the magnitude of the effects when we examined the incidence of prison misconduct.